Governor’s Award for the books about Irgiredmet - Goroshchenova, Olga (project baikal, 2023)
The Irkutsk Research Institute of Precious and Rare Metals and Diamonds (Irgiredmet) has a 150-year history. The Institute changed its name several times, was under different departments, and was classified as secret. Its main activity is research and development, comprehensive scientific and technical assessment and development of mineral deposits, design, construction and reconstruction of metallurgical enterprises. The building of Irgiredmet is located in the central part of Irkutsk on the Embankment of the Angara River. Initially, the Irkutsk gold-alloy laboratory was located on this site. In Soviet times, a monumental building was built for Irgiredmet. Designed by architect D. M. Goldstein and engineer M. F. Anikin, it is one of the main buildings in the central part of Irkutsk.